Pediatric tuberculosis consultations across 5 CDC regional tuberculosis training and medical consultation Centers - Mase, Anjeli; Ryan, Stephen; Mader, Greg; Alvarez, Ana; Armitige, Lisa; Chen, Lisa; McSherry, George; Wilson, John; Mase, Sundari; Banerjee, Ritu (Journal of clinical tuberculosis and other mycobacterial diseases, 2018)
The U.S. Centers for Disease Control and Prevention (CDC) funds five Regional Tuberculosis Training and Medical Consultation Centers (RTMCCs) that provide training and consultation for tuberculosis (TB) control and management. RTMCC utilization for assistance with diagnosis and management of TB in children has not been described. We analyzed pediatric TB consultations performed across all RTMCCs in terms of question type, provider type, and setting. The CDC medical consultation database was queried for consultations regarding patients ≤ 18 years provided between 1/1/13–4/22/15 by all RTMCCs (Curry International TB Center, Heartland National TB Center, Mayo Clinic Center for TB, New Jersey Medical School Global TB Institute, Southeastern National TB Center). Each query was categorized into multiple subject areas based on provider type, setting, consultation topic, and patient age. The 5 RTMCCs received 1164 pediatric consultation requests, representing approximately 20% of all consultations performed by the centers during the study period. Providers requesting consults were primarily physicians (46.3%) or nurses (45.0%). The majority of pediatric consult requests were from state and local public health departments (679, 58.3%) followed by hospital providers (199, 17.1%); fewer requests came from clinicians in private practice (84, 7.2%) or academic institutions (40, 3.4%). Consults addressed 14 different topics, most commonly management of children with TB disease (19.1%), latent TB infection (LTBI) (18.2%), diagnosis or laboratory testing (18.7%), and pharmacology (9.2%). Pediatric consultations accounted for approximately 20% of all consultations performed by RTMCCs during the study period. RTMCCs were utilized primarily by public health departments regarding management of TB disease, LTBI, and diagnosis or laboratory testing. The relative underutilization of the RTMCCs by clinicians in non-public health settings, who often manage children with TB exposure or infection, warrants further study. As US TB case rates decline and providers become less experienced with childhood TB, medical consultation support may become increasingly important.